Enhancing Seed Storability in Soybean Cultivars: Comparative Impact of Packaging Materials and Storage Environments - RAZIA SULTANA; KESHAVULU KUNUSOTH; M PALLAVI; K BAYYAPU REDDY; P SUJATHA; K JHANSI RANI (Seed Research, 2025)
Storage of seeds till the next sowing with appropriate packages and suitable locations is an essential segment of the seed industry. Thus, the study was conducted to identify suitable location with appropriate package material for safe seed storage until next planting season using four packaging materials (cloth bag, jute bag, HDPE bag and air tight container with drying beads) at three locations viz., Hyderabad, Nizamabad and Guntur Districts of Telangana and Andhra Pradesh, India for 10 months under ambient conditions. The experiment was initiated with two cultivars with initial germination of 93% and 90% respectively and seed moisture content (SMC) of 9.62% and 9.16% for JS 335 and JS 93-05 respectively. The experimental results revealed significant variation for seed quality parameters studied. An overall perusal of the results at three different locations indicated that air tight container using drying beads (impervious) followed by HDPE bags with SMC around 6-8% could be better packaging material than the pervious material (cloth and jute bags) irrespective of locations to maintain seed quality. Among the cultivars studied, JS 335 had higher seed quality as compared JS 93-05 during storage period. While, the Hyderabad location found better for safe seed storage as compared to other locations. Thus, commercial storage of soybean seed can be done at below 7% SMC with moisture proof packaging material, so as to maintain seed germination above seed certification standards upto 10 months.